Metabolic Engineering for Glycyrrhetinic Acid Production in Saccharomyces cerevisiae - Guan, Ruobing; Wang, Mengge; Guan, Zhonghua; Jin, Cheng-Yun; Lin, Wei; Ji, Xiao-Jun; Wei, Yongjun (Frontiers in Bioengineering and Biotechnology, 2020)
Glycyrrhetinic acid (GA) is one of the main bioactive components of licorice, and it is widely used in traditional Chinese medicine due to its hepatoprotective, immunomodulatory, anti-inflammatory and anti-viral functions. Currently, GA is mainly extracted from the roots of cultivated licorice. However, licorice only contains low amounts of GA and the amount of licorice that can be planted is limited. GA supplies are therefore limited and cannot meet the demands of growing markets. GA has a complex chemical structure, and its chemical synthesis is difficult, therefore, new strategies to produce large amounts of GA are needed. The development of metabolic engineering and emerging synthetic biology provide the opportunity to produce GA using microbial cell factories. In this review, current advances in the metabolic engineering of Saccharomyces cerevisiae for GA biosynthesis and various metabolic engineering strategies that can improve GA production by yeast are summarized. Furthermore, the advances and challenges of yeast GA production are also discussed. In summary, GA biosynthesis using metabolically engineered S. cerevisiae serves as one possible strategy for sustainable GA supply and reasonable use of traditional Chinese medical plants.